A chemometric approach to the interaction of hydrogen peroxide and thermally activated persulfate in the removal of aromatic compounds. - Faggiano, Antonio; Martínez Piernas, Ana Belén; Ricciardi, Maria; Motta, Oriana; Fiorentino, Antonino; Proto, Antonio (Elsevier, 2025)
This study evaluates the combined use of H₂O₂ and thermally activated S₂O₈2⁻ (T-PDS) for the degradation of phenolic compounds (PhOH) in wastewater, aiming to limit or eliminate sludge production. Phenolic compounds are common in industrial effluents, and their effective removal is crucial for reducing environmental impact. The study employs Response Surface Methodology (RSM) and Principal Component Analysis (PCA) to optimise critical variables such as temperature, pH, and oxidant concentrations. Optimal conditions were determined to be a temperature of 70 °C, pH 5, and a H2O2/S2O82− molar ratio of 1:6. Under these conditions, the system achieved an 89% PhOH degradation efficiency, reducing the concentration from 10 to 1.2 mg L−1 after 120 min of treatment. The kinetic analysis revealed a rapid initial reduction in PhOH concentration by 38% (from 10 to 6.2 mg L−1) within the first 15 min, followed by a slower degradation phase. This suggests a complex reaction mechanism, likely influenced by oxidant consumption and intermediate formation. The model demonstrated high precision, with R2 values of 0.99 for PhOH and S2O82−and slightly lower for H₂O₂ (R2 = 0.98). A brief cost analysis estimated the treatment cost at €6.86 per cubic meter of wastewater, showing the economic viability of the process. Additionally, eliminating sludge formation reduces operational costs related to sludge management and disposal, making the H2O2/T-PDS system a promising solution for large-scale industrial applications in sustainable wastewater treatment.
Keywords: Aguas residuales - Purificación; Aguas residuales - Oxidación; Fenoles; Biodegradación; Modelos matemáticos; Advanced oxidation processes; Dual oxidant system; Phenol degradation; Kinetic modelling; Wastewater treatment